* Mention it's configure.ac now, not configure.in.
[ginac.git] / doc / powerlaws.tex
1 \documentclass{article}
2
3 \begin{document}
4
5 \section{Power Laws}
6
7 \subsection{Definitions}
8
9 Definitions for power and log:
10 \begin{equation}\label{powerdef}
11 x^a \equiv e^{a \ln x}
12 \end{equation}
13 \begin{equation}
14 \ln x \equiv \ln |x| + i \arg(x) \mbox{ where } -\pi < \arg(x) \le \pi
15 \end{equation}
16
17 \subsection{General rules}
18
19 \begin{equation}
20 e^x e^y = e^{x+y}
21 \end{equation}
22 for arbitrary complex \(x\) and \(y\) (with~(\ref{powerdef}) we obtain
23 the rule \(x^ax^b=x^{a+b}\) since \(x^ax^b\equiv e^{a\ln x}e^{b\ln x} = 
24 e^{(a+b)\ln x}\equiv x^{a+b}\) for arbitrary complex \(a,b,x\))
25
26 \begin{equation}
27 x^{-a} = \frac{1}{x^a}
28 \end{equation}
29 for arbitrary complex \(x\) and \(a\)
30
31 \subsection{\((ax)^b=a^b x^b\)}
32
33 \subsubsection{\(b\) integer, \(x\) and \(a\) arbitrary complex}
34
35 assume \(b>0\)
36
37 \begin{eqnarray}
38 (ax)^b & = & \underbrace{(ax) \cdots (ax)}_{b \times}
39 \nonumber\\
40 & = & \underbrace{a \cdots a}_{b \times}
41       \underbrace{x \cdots x}_{b \times}
42 \nonumber\\
43 & = & a^b x^b \mbox{ q.e.d.}
44 \end{eqnarray}
45
46 if \(b<0\) (so \(b=-|b|\))
47 \begin{eqnarray}
48 (ax)^b & = & \frac{1}{(ax)^{|b|}}
49 \nonumber\\
50 & = & \frac{1}{a^{|b|} x^{|b|}}
51 \nonumber\\
52 & = & a^{-|b|} x^{-|b|}
53 \nonumber\\
54 & = & a^b x^b
55 \end{eqnarray}
56
57 \subsubsection{\(a>0\), \(x\) and \(b\) arbitrary complex}
58
59 \begin{eqnarray}
60 (ax)^b & = & e^{b \ln(ax)}
61 \nonumber\\
62 & = & e^{b (\ln |ax| + i \arg(ax))}
63 \end{eqnarray}
64
65 if \(a\) is real and positive:
66 \begin{equation}
67 \ln |ax| = \ln |a| + \ln |x| = \ln a + \ln |x|
68 \end{equation}
69 and 
70 \begin{equation}
71 \arg(ax) = \arg(x)
72 \end{equation}
73
74 So
75 \begin{eqnarray}
76 e^{b (\ln |ax| + i \arg(ax))} & = &
77 e^{b (\ln a + \ln |x| + i \arg(x))}
78 \nonumber\\
79 & = & e^{b (\ln a + \ln x)}
80 \nonumber\\
81 & = & e^{b \ln a} e^{b \ln x}
82 \nonumber\\
83 & = & a^b x^b \mbox{ q.e.d.}
84 \end{eqnarray}
85
86 \subsection{\((x^a)^b = x^{ab}\)}
87
88 \subsubsection{\(b\) integer, \(x\) and \(a\) arbitrary complex}
89
90 assume \(b>0\)
91
92 \begin{eqnarray}
93 (x^a)^b & = & \underbrace{(x^a) \cdots (x^a)}_{b \times}
94 \nonumber\\
95 & = & \underbrace{e^{a \ln x} \cdots e^{a \ln x}}_{b \times}
96 \nonumber\\
97 & = & e^{\underbrace{\scriptstyle a \ln x + \dots + a \ln x}_{b \times}}
98 \nonumber\\
99 & = & e^{a b \ln x}
100 \nonumber\\
101 & = & x^{ab} \mbox{ q.e.d.}
102 \end{eqnarray}
103
104 if \(b<0\) (so \(b=-|b|\))
105 \begin{eqnarray}
106 (x^a)^b & = & \frac{1}{(x^a)^{|b|}}
107 \nonumber\\
108 & = & \frac{1}{x^{a|b|}}
109 \nonumber\\
110 & = & x^{-a|b|}
111 \nonumber\\
112 & = & x^{ab}
113 \end{eqnarray}
114
115 \subsubsection{\(-1 < a \le 1\), \(x\) and \(b\) arbitrary complex}
116
117 We have
118 \begin{equation}
119 x^a=e^{a \ln|x| + ia\arg(x)}
120 \end{equation}
121 if \(a\) is real
122 \begin{equation}
123 |x^a|=e^{a\ln|x|}
124 \end{equation}
125 and
126 \begin{equation}
127 \arg(x^a)-a\arg(x)=2k\pi
128 \end{equation}
129 now if \(-1 < a \le 1\), then \(-\pi < a\arg(x) \le \pi\),
130 and so \(k=0\), i.e.
131 \begin{equation}
132 \arg(x^a)=a\arg(x)
133 \end{equation}
134 (Note that for \(a=-1\) this may not be true, as \(-1 \arg(x)\) may be equal to \(-\pi\).)
135 So
136 \begin{eqnarray}
137 \ln(x^a) & = & \ln|x^a| + i\arg(x^a)
138 \nonumber\\
139 & = & \ln (e^{a\ln|x|})+ia\arg(x)
140 \nonumber\\
141 & = & a \ln |x| + ia\arg(x) \mbox{ (because \(a\ln|x|\) is real)}
142 \nonumber\\
143 & = & a\ln x
144 \end{eqnarray}
145 Hence
146 \begin{eqnarray}
147 (x^a)^b & = & e^{b\ln x^a}
148 \nonumber\\
149 & = & e^{ba\ln x}
150 \nonumber\\
151 & = & x^{ab} \mbox{ q.e.d.}
152 \end{eqnarray}
153
154 proof contributed by Adam Strzebonski from Wolfram Research
155 ({\tt adams@wolfram.com}) in newsgroup {\tt sci.math.symbolic}.
156
157 \end{document}